Community planned behavior in renewable energy adoption for decarbonizing island communities - Ari Rahman; I Wayan Koko Suryawan (Journal of Sustainability Perspectives, 2026)
This study investigates the pivotal role of community behavior in adopting renewable energy as a pathway toward achieving carbon neutrality in island communities. Employing the Theory of Planned Behavior (TPB), the research examines how critical dimensions adaptive attitude, subjective norms, perceived behavioral control, and intention influence individual and collective actions for sustainable energy transitions. The findings reveal that adaptive attitude (H1) significantly impacts subjective norms (p = 0.015), suggesting that positive perceptions of renewable energy benefits, such as reduced greenhouse gas emissions and potential economic opportunities, foster widespread community support. This indicates that when individuals view renewable energy favorably, they contribute to shaping societal norms that prioritize sustainable energy adoption. Subjective norms (H2) exert a strong influence on perceived behavioral control (p < 0.001), underscoring the importance of social networks and cultural dynamics in mobilizing community participation. Furthermore, adaptive attitude (H3) directly affects intention (p = 0.064), indicating that personal beliefs and awareness about the advantages of renewable energy drive individuals' readiness to engage in sustainable practices. The results also show that subjective norms (H4) play a critical role in shaping intention (p < 0.001), emphasizing the power of social influence, including peer encouragement and collective advocacy, in motivating communities to take action. This demonstrates that societal endorsement of renewable energy creates a positive feedback loop that strengthens individuals’ intentions to act. While perceived behavioral control (H5) did not have a direct effect on intention, it remains an essential factor in addressing barriers. Finally, the study finds that intention (H6) serves as a direct driver of tangible support for renewable energy projects (p < 0.001), bridging motivation and concrete actions such as the installation of solar panels, adoption of wind energy systems, and participation in local energy cooperatives.